2020
DOI: 10.33495/jacr_v8i9.20.159
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the determinants and constraints of smallholder vegetable farmers’ adaptation capacity to climate change: A case of Bogura District, Bangladesh

Abstract: Climate change adaptation strategies are one of the best alternatives to reduce the impacts of climate change on vegetable production. This paper examined the adaptation capacity level of the vegetable growers, determinants of their adaptation decision and constraints they are facing. Data were captured through a Questionnaire survey and Focus Group Discussion (FGD) conducted with the farmers of Bogura district, Bangladesh. Frequency counts, mean, percentage, range and linear regression model, were used to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…This will greatly affect production positively because subsistence farming needs so much energy for its production. In line with this, Kabir et al (2020) reported that age within a productive age shows good labour availability in the production process. The majority (81.1%) of the cocoyam farmers were married, while 12 per cent were widow/widower and 6.7% were single.…”
Section: Farmerssupporting
confidence: 55%
“…This will greatly affect production positively because subsistence farming needs so much energy for its production. In line with this, Kabir et al (2020) reported that age within a productive age shows good labour availability in the production process. The majority (81.1%) of the cocoyam farmers were married, while 12 per cent were widow/widower and 6.7% were single.…”
Section: Farmerssupporting
confidence: 55%
“…However, lack of labour (PFI = 1.02) was the least important problem stated by the sugarcane farmers because there were available labour sources for sugarcane cultivation in the study area. Kabir et al (2020) found shortage of labor as a least significant problem in his study.…”
Section: Extent Of Problems Of Sugarcane Farmersmentioning
confidence: 87%
“…11(1): 101-108, June 2021 Odini (2014), access to extension personnel renders good sources of information for managing diversified farm activities effectively. A research carried out by Kabir et al (2020) found that extension media contact contributed significantly to the farmers' problems in Bangladesh. Pandit and Basak (2013) observed similar relationship between extension media contact and constraints faced by the farmers in commercial vegetable cultivation.…”
Section: Correlation Between Socioeconomic Characteristics and Problems Of Sugarcane Farmersmentioning
confidence: 99%
“…Maybe educated women consider other income-generating opportunities more profitable than post-processing of vegetables. However, all variables jointly explained the variance of women's attitude indicates a moderate, to a good level of strength, of the model (Kabir, et. al,, 2020).…”
Section: Resultsmentioning
confidence: 99%